ANALISIS PENGARUH ANGKA HARAPAN LAMA SEKOLAH, RATA-RATA LAMA SEKOLAH, DAN PENGELUARAN PER KAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA - A. Jauhar Mahya; Widowati Widowati (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
The Human Development Index (HDI) is one of the data and information used by local governments to measure the achievement of human development. HDI is formed by three basic dimensions, namely a long and healthy life, knowledge, and a decent standard of living. This study explain whether there is an influence and to obtain the magnitude of the influence of the expected number of years of schooling, the average length of schooling, and the per capita expenditure together on the Human Development Index in Central Java Province. This study was completed using multiple linear regression analysis with the help of SPSS 1.6 (Statistical Package for Social Sciences) software. The results of this study indicate that the expected length of schooling, average length of schooling, and per capita expenditure have a significant effect on the human development index, which is 97.8% and only 2.2% is influenced by other factors.